2018
DOI: 10.31031/nacs.2018.01.000506
|View full text |Cite
|
Sign up to set email alerts
|

Combined Photodynamic and Radiotherapy Synergistic Effect in Cancer Treatment

Abstract: This review aims to increase the success rate in the treatment of cancer when both photodynamic therapy and radiotherapy are used together as a combined therapy and it is aimed to inform this direction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…A recent review article of Yurt & Tuncel [1] reported the clinical aspects of combined photodynamic and radiotherapy synergistic effect in cancer treatment. Synergic method combining photothermal therapy (PTT) and photodynamic therapy (PDT) using nanogold particles and photosensitizers were also reported [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…A recent review article of Yurt & Tuncel [1] reported the clinical aspects of combined photodynamic and radiotherapy synergistic effect in cancer treatment. Synergic method combining photothermal therapy (PTT) and photodynamic therapy (PDT) using nanogold particles and photosensitizers were also reported [2][3][4].…”
Section: Introductionmentioning
confidence: 99%